2015
DOI: 10.1021/acs.macromol.5b02059
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Chirality in a Conjugated Polymer without Any Excess of Chiral Centers

Abstract: Chirality is typically expressed in chiral molecules, including polymers. In this work, we demonstrate that chirality can also be expressed in a polymer molecule that does not contain any excess of chiral centers; in this specific material the chirality is evoked by a specific order of manipulations ("events"). The polymer studied is an allconjugated block copoly(3-alkylthiophene), in which the first block contains exactly the same amount of (S)-enantiomers as the second block (R)-enantiomers. Moreover, to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…166,[180][181][182] Our research group prepared a block copolymer in which each block is a random copolymer. 183…”
Section: All-conjugated Block Copolymers With the Same Aromatic Moietiesmentioning
confidence: 99%
“…166,[180][181][182] Our research group prepared a block copolymer in which each block is a random copolymer. 183…”
Section: All-conjugated Block Copolymers With the Same Aromatic Moietiesmentioning
confidence: 99%
“…They further synthesized a block copoly(3-alkylthiophene) 26 and investigated its aggregation, in which both blocks were a copolymer of a chiral monomer and an achiral monomer. 36 The (S)-and (R)block contained exactly the same amount of (S)-and (R)enantiomers as side chain, respectively, rendering the lack of any excess of chiral centers. Because the amine and octyl group endowed a different solubility for the (R)-and (S)-block, the (S)-block aggregated first thus determined the whole chirality of the copolymer and the followed aggregation of the (R)-block further enhanced the chiral response.…”
Section: Introductionmentioning
confidence: 99%
“…27 We have demonstrated that the less soluble block of a block copolymer aggregates first and imposes its stacking to the second, more soluble block, whether this stacking is expected for the homopolymer of that second block or not. 26,[28][29][30][31][32] Apart from the nature of the blocks, also their degree of polymerization (DP) plays a role: a higher DP results in a lower solubility. Finally, we hypothesize that also the end-group is of importance.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of block copolymers of which both blocks are the same but consist of a different enantiomer (Scheme 1.2), enables us to visualize the self-assembly of the block copolymer, and more specifically which block aggregates first and imposes its stacking. 32 More precisely, block copolymers with a different percentage of (R) monomer compared to (S) monomer are synthesized for each different end-group (Scheme 1.3).…”
Section: Introductionmentioning
confidence: 99%